1952
DOI: 10.1063/1.1700780
|View full text |Cite
|
Sign up to set email alerts
|

The Dielectric Properties of Water in Solutions

Abstract: Results of dielectric constant and loss measurements at λ=9.22, 3.175, and 1.264 cm are given for a wide variety of aqueous solutions of ions and organic molecules. The water relaxation time is shortened by positive ions and lengthened by hydrogen bond-forming molecules. The properties of water are treated by a statistical method in which the numbers of molecules in four, three, two, one, and zero-bonded states are estimated from dielectric and latent heat data. Fair agreement with experiment is obtained in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
170
0
8

Year Published

1969
1969
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(191 citation statements)
references
References 30 publications
13
170
0
8
Order By: Relevance
“…Average number of H bonds per water molecule at various temperatures, as extracted using different techniques in the past. X ray diffraction study at 100 MPa (Gorbaty & Demianets, 1983); NMR (Hoffmann & Conradi, 1997); Water electronic study (Schwegler et al, 2000); Quantum cluster equilibrium method (Lehmann et al, 2009); TIP4P (Prendergast & Galli, 2006); + CPAIMD (Lee & Tuckerman, 2006); ♦ Neutron diffraction (Soper et al, 1997); IR (Luck, 1967); TEY-NEXAFS (Smith et al, 2004); SXEER (Myneni et al 2002); IR at 250 atm (Bondarenko & Gorbaty, 1991); Latent Heat (Haggis et al, 1952); Statistical mechanics (Suresh et al, 2000); Electronic structure study (He et al 2007 (Kalinichev & Bass, 1997); Ab initio (Kuo & Mundy, 2004); FPMD (Hetenyi et al, 2004); X-ray absorption (Wernet et al, 2004). We first start with a discussion on the paper published by Smith et al (Smith et al, 2004) which concluded that HB n   ~3.3.…”
Section: Structure Of Bulk Watermentioning
confidence: 99%
“…Average number of H bonds per water molecule at various temperatures, as extracted using different techniques in the past. X ray diffraction study at 100 MPa (Gorbaty & Demianets, 1983); NMR (Hoffmann & Conradi, 1997); Water electronic study (Schwegler et al, 2000); Quantum cluster equilibrium method (Lehmann et al, 2009); TIP4P (Prendergast & Galli, 2006); + CPAIMD (Lee & Tuckerman, 2006); ♦ Neutron diffraction (Soper et al, 1997); IR (Luck, 1967); TEY-NEXAFS (Smith et al, 2004); SXEER (Myneni et al 2002); IR at 250 atm (Bondarenko & Gorbaty, 1991); Latent Heat (Haggis et al, 1952); Statistical mechanics (Suresh et al, 2000); Electronic structure study (He et al 2007 (Kalinichev & Bass, 1997); Ab initio (Kuo & Mundy, 2004); FPMD (Hetenyi et al, 2004); X-ray absorption (Wernet et al, 2004). We first start with a discussion on the paper published by Smith et al (Smith et al, 2004) which concluded that HB n   ~3.3.…”
Section: Structure Of Bulk Watermentioning
confidence: 99%
“…(1). Thus, the dissociation equilibrium of ammonium ion in a waternmethanol mixture is described as: (7) Here x denotes a fraction of alkoxonium ion formed and is given by the following equation through the equilibrium constant, k, of Eq. (1): (8) activities of water and methanol being approximated to be equal to their mole fractions.…”
mentioning
confidence: 99%
“…For this factor can be separated the specific component of influence that is the change of phase-structural state of membrane [19][20][21]. The structural reconstructions of erythrocyte membranes induced by the temperature cause the changes of solvent (water) structure [22,23]. The possibility of the use of UHF-dielectrometry method for the study of relaxation frequency of substances particularly the dielectric relaxation frequency of the water molecules in erythrocyte membranes is determined by the fact that the molecules of the bound water and dissolved substance in centimeter wavelengths diaposon are less movable than the molecules of the free water [24,25].…”
Section: The Ground Of Researchmentioning
confidence: 99%